1998
DOI: 10.2136/sssaj1998.03615995006200010030x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for Temporal Changes in Soil Salinity using Electromagnetic Induction Techniques

Abstract: Electromagnetic induction surveys are often used in practice to estimate field‐scale soil salinity patterns, and to infer changing salinity conditions with time. We developed a statistical monitoring strategy that uses electromagnetic induction data and repetitive soil sampling to measure changing soil salinity conditions. This monitoring approach requires (i) the estimation of a conditional regression model that is capable of predicting soil salinity from electromagnetic (EM) survey data, and (ii) the acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 10 publications
0
57
1
1
Order By: Relevance
“…This was the case for the Ebro valley (Amezketa, 2006) and specifically for the Flumen irrigation district (López-Bruna and Herrero, 1996;Lesch et al, 1998;Herrero et al, 2003). The EM38 successfully mapped soil salinity of small 75 plots (< 1 ha).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was the case for the Ebro valley (Amezketa, 2006) and specifically for the Flumen irrigation district (López-Bruna and Herrero, 1996;Lesch et al, 1998;Herrero et al, 2003). The EM38 successfully mapped soil salinity of small 75 plots (< 1 ha).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, it is very improbable for the salinity to proportionally change temporally, a condition required (Lesch et al, 1998) to maintain the calibration equations between two sampling dates. …”
mentioning
confidence: 99%
“…Lesch et al (1998) discussed another approach that can test for change in the mean value as well as for a dynamic spatial variation between two time instants. Dynamic spatial variation refers to the spatially variable change of a soil property between two time instants, i.e., the change is not the same between two time instants for each location.…”
Section: Dynamic Spatial Variationmentioning
confidence: 99%
“…To test for the existence of dynamic spatial variation, Lesch et al (1998) identified different steps. First of all, the pairs of soil data obtained at a first time instant (y and z), from n space locations, are used to establish a calibration equation based on the regression model:…”
Section: Dynamic Spatial Variationmentioning
confidence: 99%
See 1 more Smart Citation